Conservative management of uterine artery pseudoaneurysm occurring during treatment of gestational trophoblastic disease: A case report. Issue 10 (6th August 2020) - Hayata, Eijiro; Komiyama, Shinichi; Nagashima, Masaru; Taniguchi, Tomoko; Morita, Mineto
Abstract: Uterine artery pseudoaneurysm (UAP) is a rare disease that causes genital bleeding during the postpartum period after cesarean section. Uterine artery embolization (UAE) is an effective procedure for UAP. UAP was unexpectedly encountered in a patient with gestational trophoblastic disease; however, this patient was conservatively managed without UAE. UAP can occur during treatment for gestational trophoblastic disease. Since asymptomatic UAP may spontaneously disappear, in the selection of conservative treatment, it is important to carefully monitor patients using transvaginal ultrasonography focusing on the size of the UAP and the speed of internal blood flow.